Harry Potter and the Half-Blood Prince - Rowling, J. K. (Arthur A. Levine Books, 2005)
Sixth-year Hogwarts student Harry Potter gains valuable insights into the boy Voldemort once was, even as his own world is transformed by maturing friendships, schoolwork assistance from an unexpected source, and devastating losses.